The Impact of The Government Accounting System on The Application of Program Budgeting and Performance In The Iraqi Environment - Sarmad Hussein Atiyah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study addresses the challenges and opportunities associated with developing and reforming the government budget and accounting system, with a particular focus on Iraq and similar regional contexts. The research highlights the importance of adopting modern methods such as accrual accounting and performance-based budgeting, and strengthening financial control mechanisms to enhance transparency, accountability, and efficiency in government units. Previous studies have emphasized the role of internal auditing, financial information systems, and management accounting in improving budget performance and reducing financial irregularities. International experience has also shown that adopting advanced budgeting practices contributes to combating corruption and enhancing the effectiveness of institutional performance. The study aims to provide a comprehensive understanding of the theoretical and practical dimensions of general budget reform by reviewing previous literature and analyzing applied models in Iraq and other countries. The paper also aims to develop an integrated framework that supports decision-makers and policymakers in implementing budget practices in line with international standards. This contributes not only to achieving financial discipline but also to ensuring the efficient allocation of resources and enhancing the sustainability of public financial systems.